Horse odor exploration behavior is influenced by pregnancy and age - Rørvang, Maria Vilain; Nicova, Klára; Yngvesson, Jenny (Frontiers in Behavioral Neuroscience, 2022)
In spite of a highly developed olfactory apparatus of horses, implying a high adaptive value, research on equine olfaction is sparse. Our limited knowledge on equine olfaction poses a risk that horse behavior does not match human expectations, as horses might react fearful when exposed to certain odors, which humans do not consider as frightening. The benefit of acquiring more knowledge of equine olfaction is therefore twofold; 1) it can aid the understanding of horse behavior and hence reduce the risk of dangerous situations, and 2) there may be unexplored potential of using odors in several practical situations where humans interact with horses. This study investigated behavior and olfactory sensitivity of 35 Icelandic horses who were presented with four odors: peppermint, orange, lavender and cedar wood in a Habituation/Dishabituation paradigm. The response variables were sniffing duration per presentation and behavioral reaction (licking, biting, snorting, and backing), and data were analyzed for potential effects of age, sex and pregnancy. Results showed that habituation occurred between successive odor presentations (1st vs 2nd and 2nd vs 3rd presentations: P < 0.001), and dishabituation occurred when a new odor was presented (1st vs 3rd presentations: P < 0.001). Horses were thus able to detect and distinguish between all four odors, but expressed significantly longer sniffing duration when exposed to peppermint (peppermint vs orange, lavender and cedar wood: P < 0.001). More horses expressed licking when presented to peppermint compared to cedar wood and lavender (P = 0.0068). Pregnant mares sniffed odors less than non-pregnant mares (P = 0.030), young horses (age 0-5 years) sniffed cedar wood for longer than old horses (P = 0.030), whereas sex had no effect (P > 0.050). The results show that horses’ odor exploration behavior and interest in odors varies with age and pregnancy and that horses naïve to the taste of a substrate, may be able to link smell with taste, which has not been described before. These results can aid our understanding of horses’ behavioral reactions to odors, and in the future, it may be possible to relate these to the physiology and health of horses.